By the Honorable William Pitkin, Esq ; governor of the English colony of Connecticut ... A proclamation : ... Thursday the seventeenth day of November next, to be observed as a day of public thanksgiving ... Given under my hand in the Council chamber in New-Haven, the 24th day of October ... 1768 (Printed by Thomas & Samuel Green, 1768)
October 24, 1768 broadside issued by Governor William Pitkin of Connecticut, proclaiming November 17th as a day of public thanksgiving for the good health of the royal family and continued rights enjoyed by the colony, as well as a good harvest.